Thermal behaviour of mixed blended ashes aerated concrete - Zalani, Rahmah (2015)
This research investigated the used of bottom ash and palm oil fuel ash (POFA) from Tanjung Bin Power Plant and Kahang Palm Oil Mill respectively as sand replacement to produce mixed blended ashes aerated concrete. The goal is to determine characterization and thermal behaviour of the product and to compare the best POFA ratio replacement with existing commercial products. POFA was used as sand replacement at 0%, 10%, 20% and 30% by weight with fixed amount of bottom ash. A small-scale wall structure models was developed to study thermal behaviour of product through conduction and convection mechanism heat transfer for seven sunny days at 24-hour. The result showed that thermal conductivity of P30% achieved 0.48 W/mK, 81% lower than conventional concrete. P30% gave the best insulation result among different POFA ratio replacement with 122 minutes in time lag. As for the comparison with commercial aerated concrete, P30% achieved fastest thermal absorption rate with an hour earlier to reach absorption peak and 50% more in thermal mass. This gave better indoor thermal comfort. P30% also exhibited fastest adiabatic state rate with two hour earlier compared to commercial aerated concrete. Good insulation property also gave better result in lessen Urban Heat Island effect at night. However, the stored heat inside the wall contributed towards hotter indoor temperature compared to commercial aerated concrete. Further study in building design alteration might help in mitigating this drawback such as providing better air circulation with cooling chimney and window.